Whither Proxies? - Švob, Goran (2005)
Contemporary logical literature invariably reduces relations to sets of ordered n-tuples. In case of identity relation such a practice presents special problems.
Tekst će biti objavljen zajedno s drugim dijelom teksta u posebnom zborniku (izdavač Parerga, Berlin) časopisa Studia Hermeneutica.
Projekt MZOS
ENG